Trade productivity upgrading, trade fragmentation, and FDI in manufacturing: The Asian development experience - Jesse Mora; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2012)
This paper examines the experience of 10 - Asian countries with respect to growth, trade and FDI. It explores relationships between the nature of exports and imports and growth, as well as the relevance of FDI as a channel for these relationships. We find that FDI is often positively correlated with higher productivity levels in exports and imports. The effect for imports is particularly apparent for imported intermediate goods, reflecting the emergence of greater trade fragmentation. In turn, both imported intermediates and exports that are associated with higher productivity levels are positively correlated with per capita GDP. This paper therefore brings together empirical evidence that integrates discussions of FDI, trade fragmentation and improvements in the productivity of traded goods.
Keywords: O1; O24; F14; O33; 330; international trade; trade policy; product upgrading; trade fragmentation; vertical specialization; FDI and economic development